1996
DOI: 10.1103/physrevb.53.8340
|View full text |Cite
|
Sign up to set email alerts
|

Localization of electromagnetic waves in two-dimensional disordered systems

Abstract: We calculate the average transmission for s-and p-polarized electromagnetic ͑EM͒ waves and consequently the localization length of two-dimensional ͑2D͒ disordered systems which are periodic on the average; the periodic systems form a square lattice consisting of infinitely long cylinders parallel to each other and embedded in a different dielectric medium. In particular, we study the dependence of the localization length on the frequency, the dielectric function ratio between the scatterer and the background, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
76
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 36 publications
10
76
0
Order By: Relevance
“…In two dimensions, it was found that higher order photonic gaps close quickly with increasing disorder, while the lower order gaps, especially the first one, remain open for large values of the disorder [42]. For all frequencies however, light becomes localized.…”
Section: Photonic Band Gap Materialsmentioning
confidence: 97%
“…In two dimensions, it was found that higher order photonic gaps close quickly with increasing disorder, while the lower order gaps, especially the first one, remain open for large values of the disorder [42]. For all frequencies however, light becomes localized.…”
Section: Photonic Band Gap Materialsmentioning
confidence: 97%
“…The role Mie resonances play in the gap formation process in PCs has been understood in analysing the effect of disorder [10,11]. In the present paper we shall take advantage of this concept to reveal the physical origin of the spectral domains with low LDOS for QPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Through different photonic architectures it is possible to augment the optical absorption by, for instance, trapping light within ultra-thin films [14], or even manipulate the photon density of state [15] or slowing down light in absorbing thin films. This can be achieved by periodic photonic structures [14,15] or disordered ones [19][20][21], as it has been recently proposed in a two-dimensional system [22] in which disorder modes are on the verge of light (Anderson) localization [23][24][25].…”
Section: -Introductionmentioning
confidence: 99%